Convex Optimization Algorithm for Maximizing Directivity of Conformal Array With DRR Constraint - Chao Liu; Tongtao Zhu; Junjie Qian; Lei Zhang; Xiaoyuan Zhang (International Journal of Antennas and Propagation)
The inconsistency of conformal array elements poses a huge challenge to pattern synthesis. Based on convex optimization theory, this paper proposes a novel directivity pattern synthesis method. It can maximize the directivity of dual-polarized conformal arrays with a low dynamic range ratio (DRR). Firstly, the directivity function is presented under a dual-polarized conformal array. Then the pattern synthesis based on maximizing directivity is summarized as a multiconstraint optimization problem. In addition, the DRR constraint is introduced to control the weight range. By using Taylor expansion, the problem is transformed into a convex optimization problem and solved iteratively. Finally, simulation results demonstrate that the proposed method can effectively achieve a good directivity pattern with low sidelobe level (SLL) and low DRR.